Menafsirkan kalimat dari sebuah artikel “islam agama damai” - Rozik, Muhammad Habibur (Maliki Interdisciplinary Journal, 2025)
This study analyzes the interpretation of meaning in the sentences of the article entitled "Islam: Religion of Peace". This article was analyzed using qualitative descriptive methods and semantic theory. This study provides a solution to the problem of how to interpret the meaning of the sentences in the article. This problem can be answered by using semantic theory or the theory of language meaning. Based on the results of the study, the interpretation of the meaning of the sentences found in the article "Islam: Religion of Peace" is that Islam is a teaching and religion that believes in God, the Prophet Muhammad, and the Qur'an as a holy book. Islam has an ideology of peace but there are deviations from the model (Islamic teachings). One must distinguish between the meaning of language from the speaker's and listener's perspectives. Intention or assumption is private, while interpretation of meaning is public and shared by both the speaker/writer and the listener/reader.